Health Risk Assessment of Some Heavy Metal Residues in Some Fish Retailed in Sharkia Governorate, Egypt - Morshdy, Alaa Eldin M.A.; El-tahlawy, Ahmed S.; Abd El Galil, Ghada M.; El Bayomi, Rasha M.; Darwish, Wageh (Journal of Advanced Veterinary Research, 2023)
The aim of this study was to explore the residual concentrations of four heavy metals; mercury (Hg), arsenic (As), lead (Pb), and cadmium (Cd) in Mullet, Brush tooth lizard, and Coral fish collected from fish markets in Zagazig city, Sharkia Governorate, Egypt. Besides, metal’s dietary intake and public health risk were calculated. Atomic absorption spectrometry (AAS) was used to analyze these toxic heavy metals in 60 fish samples of Mullet, Brush tooth lizard, and Coral ( 20 of each). The concentration (mg/ kg) of Hg were the same value (0.02 ± 0.01) in Mullet, Brush tooth lizard, and Coral fish. However, for As were 0.35 ± 0.10, 0.32 ± 0.10, and 0.30 ± 0.08, respectively; meanwhile, Pb concentration was 0.09 ± 0.04 for both Mullet and Brush tooth lizard and it was 0.10 ± 0.04 for Coral fish Cd concentrations were 0.02 ± 0.01 in all examined fish. The estimated daily intake (EDI) of Hg, As, Pb, and Cd were 0.011, 0.191, , 0.049 and 0.011µg/ kg BW/ day , respectively in Mullet; 0.011, 0.174, 0.049, and 0.011 µg/ kg BW/ day in, respectively Brush tooth lizard; 0.011, 0.163, 0.054, and 0.011 µg/ kg BW/ day , respectively in Coral fish, that was below the tolerable daily intake (TDI) recommended by Joint Expert Committee on Food Additives (JECFA). The Target hazard quotient (THQ) of Hg, As, Pb, and Cd from consumption of examined fish was less than one which means that there was no hazard from consumption of these fish.